2014
DOI: 10.1016/j.ctcp.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive patients' preferences for complementary and alternative medicine and the influence of these preferences on the adherence to prescribed medication

Abstract: Local health care systems should provide patients with alternative health services that suit their requests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
2
8
0
3
Order By: Relevance
“…This calls for efforts to get more hypertensive patients on the health insurance scheme to lessen their burden of buying [7]. Our findings revealed a significant association between CAM use and the experience of antihypertensive medication side effects, confirming the finding reported by Lee et al, 2014, that majority of their respondents had negative perceptions of western medicine due to its side effects, hence adjusting their prescribed antihypertensive drugs with CAM [27].…”
Section: Discussionsupporting
confidence: 85%
“…This calls for efforts to get more hypertensive patients on the health insurance scheme to lessen their burden of buying [7]. Our findings revealed a significant association between CAM use and the experience of antihypertensive medication side effects, confirming the finding reported by Lee et al, 2014, that majority of their respondents had negative perceptions of western medicine due to its side effects, hence adjusting their prescribed antihypertensive drugs with CAM [27].…”
Section: Discussionsupporting
confidence: 85%
“…One, using mixed methods, including interviews with health workers and patients, concluded that use of TCAM, either to supplement or replace WM, was common 13 . This view was supported in two further studies, one comprising in-depth interviews with 10 patients in a university clinic 38 and another in a community clinic 28 . In both, many patients rejected WM, at least initially, reducing their prescribed dosage of western drugs and taking TCAM instead or in addition to the western ones, and/or taking medication (both TCAM and WM) only when symptoms were evident.…”
Section: Long Term Managemenmentioning
confidence: 80%
“…Qualitative studies in Malaysia 27,35,38 reported patients who declined treatment, which the authors attributed to being in denial of or being confused about treatment, although some overcame denial when faced with adverse health implications. Studies in both countries reported patient concerns about the cost of lifelong treatment 24,29,37 and side effects 13,22,28,31,37 . In particular, some were concerned that they might become dependent on medication, or suspected that prolonged use of medication might harm them, concerns often perpetuated by family members and friends of patients 22 .…”
Section: Medical Clinic Of Kuala Lumpurmentioning
confidence: 99%
See 2 more Smart Citations